Comparison of Beran estimator using Nadaraya-Waston and Prestley-chao weights in estimating the conditional survival function of breast cancer patients - الوكيل علي عبد الحسين; عبد علي مها محمد; رشيد امل هادي (Journal of Economics and Administrative Sciences, 2018)
This study includes the application of non-parametric methods in estimating the conditional survival function of the Beran method using both the Nadaraya-Waston and the Priestley-chao weights and using data for Interval censored and Right censored of breast cancer and two types of treatment, Chemotherapy and radiation therapy Considering age is continuous variable, through using (MATLAB) use of the (MSE) To compare weights The results showed a superior weight (Nadaraya-Waston) in estimating the survival function and condition of Both for chemotherapy and radiation therapy.